Guidelines and recommendations on yeast cell death nomenclature - Carmona-Gutierrez, Didac; Wölfl, Stefan (Microbial cell, 2018)
Guidelines and recommendations on yeast cell death nomenclature - Elucidating the biology of yeast in its full complexity has major implications for science, medicine and industry. One of the most critical processes determining yeast life and physiology is cellular demise. However, the investigation of yeast cell death is a relatively young field, and a widely accepted set of concepts and terms is still missing. Here, we propose unified criteria for the definition of accidental, regulated, and programmed (...)
Gesehen am 29.03.2019